Penerapan Metode Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) Dalam Penentuan Media Promosi Terbaik - Rajiansyah, Rajiansyah; Rizawanti, Riftika (Building of Informatics, Technology and Science (BITS), 2024)
The development of increasingly sophisticated technology provides a function which assists salespeople in promoting a product using technology. With the existence of technology, a seller can use this technology as a media tool for the promotion of the products they are marketing or selling. Promotional media is a way that is used by entrepreneurs in conveying, spreading, and offering the products or services they sell so that consumers are interested in buying. In helping carry out promotional media, it is necessary to have social media, where social media is useful or one of the tools used to promote goods or services to consumers. However, as an entrepreneur the selection of a promotional media tool can be a consideration for an entrepreneur. And in solving a problem researchers really need criteria including Location, Fisheries, Cost and Target Market. So with that researchers really need tools in making decisions using methods that can produce values ​​that are in accordance with the expectations of the authors. The tool is SPK and the method used is TOPSIS. So from this it can be concluded that the best promotional media falls on alternative A3 on behalf of Facebook with the first rank with the highest score of 0.953